Effect of Short Sleep Duration on the Risk of Cardiovascular Diseases: A Meta-Analysis - Anas Rahmad Hidayat; Harpeni Siswatibudi; R. Haryo Nugroho Purwokusumo (Journal of Epidemiology and Public Health, 2025)
Background: Understanding the impact of short sleep duration on cardiovascular disease incidence is crucial for comprehending its potential health implications. This study aimed to analyze and estimate the magnitude of the effect of short sleep duration on the risk of cardiovascular disease incidence based on similar previous primary studies.Subjects and Method: This research is a systematic review and meta-analysis conducted by following the PRISMA flow diagram and PICO model. Population: general population without prior cardiovascular diseases, Intervention: short sleep duration, Comparison: adequate sleep duration, and Outcome: the Incidence of cardiovascular diseases. The process of searching for articles through Google Scholar, ProQuest, and PubMed journal databases by selecting articles published from 2010 to 2024. The keywords used include: "Cardiovascular Diseases," AND "Incidence," AND "Sleep Duration," AND "cohort Studies. The inclusion criteria were full paper articles, open access with a cohort study design, and articles in English. Data were analyzed using RevMan 5.3.Results: A total of 9 cohort studies involving 564,287 respondents from Africa, Europe, and Asia were selected for a systematic review and meta-analysis. The results of the meta-analysis showed that people with short sleep duration had a 1.20 times risk of experiencing cardiovascular disease compared to people with adequate sleep duration (aHR = 1.20; 95% Cl = 1.14 to 1.25; p<0.001). This meta-analysis has heterogeneity I2= 39%, so it uses a fixed effect model.Conclusion: Insufficient sleep duration could elevate the likelihood of cardiovascular disease occurrence.